Phagocytic receptors regulate Drosophila larval growth - Nagaosa, Kaz (Narra X, 2025)
Drosophila melanogaster is a key model organism for biological research due to its genetic manipulability and high degree of evolutionary conservation with humans. Phagocytic receptors play a central role in apoptotic cell clearance, a fundamental process that is highly conserved across species. Previous studies have identified two major phagocytic receptors in Drosophila: integrin αPS3βν and Draper, both of which contribute to apoptotic cell removal. However, the physiological significance of these receptors under normal developmental conditions remains unclear. Therefore, the aim of this study was to investigate the role of these receptors in developmental timing. The results demonstrated that double mutants lacking both receptors exhibited significant developmental delays, especially during the larval stage (p<0.001). Moreover, tissue-specific knockdown experiments revealed that phagocytic receptors within the fat body are mainly involved in regulating developmental timing (p=0.028). Further results established that nutrient availability influenced the extent of growth delay, suggesting that these receptors may play a role in nutrient-dependent growth regulation. Taken together, these findings suggest that phagocytic receptors contribute to maintaining proper growth timing in Drosophila larvae, potentially through energy metabolism pathways.